PERSPEKTIF JANDA KRISTEN BATAK TOBA TERHADAP PERKAWINAN DALAM KONTEKS BUDAYA DAN AGAMA - Anastecia Siagian (LP2M Universitas Muslim Nusantara Al Washliyah, 2025)
Marriage in Batak Toba culture is sacred, not only binding two individuals but also the extended family. This bond has social and cultural consequences, especially for women who become widows. The status of widows in Batak Toba society has its own dynamics, influenced by customs, religion, and social norms. The decision to remarry or remain single is complex because of cultural and religious factors that shape their perceptions of second marriages. This study analyzes the perspectives of Batak Toba Christian widows on marriage in the context of culture and religion. Using a qualitative approach and phenomenological method, this study explores the experiences of Christian widows in Urung Kompas Village, Rantauprapat City. Data were collected through interviews, observations, and literature studies. The results of the study show that the decision of widows to remarry or not is influenced by culture and religion. Although Christianity gives freedom to remarry, customs and social expectations often make it difficult. Many widows experience a dilemma between religious beliefs and cultural norms. This shows the relationship between culture and religion in shaping views on second marriages. It is hoped that society will appreciate their choices more and provide support for the decisions they make.